2020
DOI: 10.3390/nu12051320
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Preoperative Parenteral Nutrition

Abstract: Malnutrition is associated with poor surgical outcomes, and therefore optimizing nutritional status preoperatively is very important. The purpose of this paper is to review the literature related to preoperative parenteral nutrition (PN) and to provide current evidence based guidance. A systemic online search of PubMed, Medline, and Cochrane Databases from January 1990 to February 2020 was done. Sixteen studies were included in this narrative review, including four meta-analyses and twelve clinical trials. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
0
23
0
7
Order By: Relevance
“…It is thus necessary to improve the nutritional status of these patients with short-term nutritional supplementation. PN provides an adequate and reliable amount of macronutrients and micronutrients, and the intravenous route of administration of nutrients may also allow for rapid improvement in nitrogen balance, increased muscle mass, faster recovery from surgery, improved immune function, and a decrease in the number of general and infectious complications [22]. Low preoperative serum levels of total proteins, albumin, prealbumin, or transferrin have been associated with increased surgical infections, increased morbidity and mortality, and increased hospital stay [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…It is thus necessary to improve the nutritional status of these patients with short-term nutritional supplementation. PN provides an adequate and reliable amount of macronutrients and micronutrients, and the intravenous route of administration of nutrients may also allow for rapid improvement in nitrogen balance, increased muscle mass, faster recovery from surgery, improved immune function, and a decrease in the number of general and infectious complications [22]. Low preoperative serum levels of total proteins, albumin, prealbumin, or transferrin have been associated with increased surgical infections, increased morbidity and mortality, and increased hospital stay [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…6 Total parenteral nutrition (TPN) is indicated for patients who do not meet daily nutritional needs through oral and/or enteral food, have severe malnutrition, or those with intestinal obstruction, high-output fistulas, severe bleeding, or when the microbiota is dysfunctional during periods of disease activity. 6,16,17 The use of preoperative TPN is directly related to a decrease in postoperative complications such as anastomotic dehiscences, thromboembolic events, and septic complications in malnourished patients with CD. 22 A meta-analysis study showed that nutritional support by enteral or parenteral nutrition in the preoperative period reduces complications in the postoperative period in IBD patients.…”
Section: How To Perform Nutritional Optimization?mentioning
confidence: 99%
“…1 The purpose of TPN in the preoperative period is to restore energy and protein storage, reduce and/or correct micronutrient deficiencies, in addition to preventing postsurgical malnutrition in patients at nutritional risk. 17 The duration of TPN in the preoperative period generally varies from 5 to 90 days, and most studies show a period of 7 to 14 days as the ideal. 12,17,23 The association of EEN and TPN should be considered in patients who need nutritional support of more than 60% for the daily needs that cannot be achieved by EEN alone.…”
Section: How To Perform Nutritional Optimization?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition support in malnourished patients can reduce the risk of postoperative complications such as surgical site infections and gastrointestinal complications (6)(7)(8). Selection of proper assessment tools is the key step for early diagnosis and treatment of malnutrition (9).…”
Section: Introductionmentioning
confidence: 99%